2023
DOI: 10.3390/jcm12051784
|View full text |Cite
|
Sign up to set email alerts
|

Severity and Longitudinal Course of Depression, Anxiety and Post-Traumatic Stress in Paediatric and Young Adult Cancer Patients: A Systematic Review and Meta-Analysis

Abstract: Background: A diagnosis of cancer and treatment may constitute a highly traumatic period for paediatric cancer patients (PYACPs). However, no review has comprehensively analysed how the mental health of PYACPs is acutely affected and the longitudinal course. Methods: This systematic review followed PRISMA guidelines. Comprehensive searches of databases were conducted to identify studies of depression, anxiety and post-traumatic stress symptoms in PYACPs. Random effects meta-analyses were used for the primary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 61 publications
2
5
0
2
Order By: Relevance
“…We also found that symptoms of anxiety, depression, and PTSD among children and adolescents diagnosed with cancer decreased over time; these ndings are supported by other longitudinal studies [26][27][28]. Other research has shown that a healthy family environment is a strong protective factor against the development of these disorders, as well as improving the quality of life of children and adolescents diagnosed with cancer [29,30]. In Oman, support extended by family members and friends to cancer patients has been observed to signi cantly reduce mental distress and alleviate the adverse side-effects associated with cancer treatment [22].…”
Section: Discussionsupporting
confidence: 85%
“…We also found that symptoms of anxiety, depression, and PTSD among children and adolescents diagnosed with cancer decreased over time; these ndings are supported by other longitudinal studies [26][27][28]. Other research has shown that a healthy family environment is a strong protective factor against the development of these disorders, as well as improving the quality of life of children and adolescents diagnosed with cancer [29,30]. In Oman, support extended by family members and friends to cancer patients has been observed to signi cantly reduce mental distress and alleviate the adverse side-effects associated with cancer treatment [22].…”
Section: Discussionsupporting
confidence: 85%
“…We also found that symptoms of anxiety, depression, and PTSD among children and adolescents diagnosed with cancer decreased over time; these findings are supported by other longitudinal studies [ 27 29 ]. Other research has shown that a healthy family environment is a strong protective factor against the development of these disorders, as well as improving the quality of life of children and adolescents diagnosed with cancer [ 30 , 31 ]. In Oman, support extended by family members and friends to cancer patients has been observed to significantly reduce mental distress and alleviate the adverse side-effects associated with cancer treatment [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thromboembolic phenomena are one of many deleterious ways cancer and its treatment can affect the cardiovascular system [51,52]. Overall, cancer and its treatment are associated with a host of adverse effects that clinicians must be cognisant of in order to optimise patient care [53,54].…”
Section: Discussionmentioning
confidence: 99%